Treatment uptake by individuals infected with Plasmodium falciparum in rural Gambia, West Africa. - von Seidlein, Lorenz (World Health Organization, 2002)
OBJECTIVE: To find out what proportion of Plasmodium falciparum infections are treated in rural Gambia. METHODS: Subjects from four villages in the Gambia were followed over nine months through visits to village health workers. Monthly cross-sectional malaria surveys measured the prevalence of P. falciparum infection. Linked databases were searched for treatment requests. Treated cases were individuals with parasitaemia who requested treatment during narrow or extended periods (14 or 28 days, respectively) before or after a positive blood film was obtained. FINDINGS: Parasite prevalence peaked in November 1998, when 399/653 (61%) individuals had parasitaemia. Parasite prevalence was highest throughout the study in children aged 5-10 years. Although access to treatment was better than in most of sub-Saharan Africa, only 20% of infected individuals sought medical treatment up to 14 days before or after a positive blood film. Within two months of a positive blood film, 199/726 (27%) individuals with parasitaemia requested treatment. Despite easy access to health care, less than half (42%) of those with parasite densities consistent with malaria attacks (5000/ l) requested treatment. High parasite density and infection during October-November were associated with more frequent treatment requests. Self-treatment was infrequent in study villages: in 3/120 (2.5%) households antimalarial drugs had been used in the preceding malaria season. CONCLUSION: Many P. falciparum infections may be untreated because of their subclinical nature. Intermittent presumptive treatment may reduce morbidity and mortality. It is likely that not all untreated infections were asymptomatic. Qualitative research should explore barriers to treatment uptake, to allow educational interventions to be planned.